Seasonal, Sex- and Plant Size-Related Effects on Photoinhibition and Photoprotection in the Dioecious Mediterranean Dwarf Palm, Chamaerops humilis - Morales, Melanie; Pintó-Marijuan, Marta; Munné-Bosch, Sergi (Frontiers in Plant Science, 2016)
In Mediterranean-type ecosystems plants are exposed to several adverse environmental conditions throughout the year, ranging from drought stress during the warm and dry summers to chilling stress due to the typical drop in temperatures during winters. Here we evaluated the ecophysiological response, in terms of photoinhibition and photoprotection, of the dioecious Mediterranean palm, Chamaerops humilis to seasonal variations in environmental conditions. Furthermore, we considered as well the influence of plant size, maturity and sexual dimorphism. Results showed evidence of winter photoinhibition, with a marked decrease of the Fv/Fm ratio below 0.7 between January and March, which was coincident with the lowest temperatures. During this period, the de-epoxidation state of the xanthophyll cycle and zeaxanthin levels increased, which might serve as a photoprotection mechanism, owing the full recovery from winter photoinhibition during spring. Furthermore, mature plants showed lower chlorophyll levels and higher β-carotene levels per unit of chlorophyll than juvenile plants, and females displayed lower leaf water contents and higher photoinhibition than males during summer, probably due to increased reproductive effort of females. However, neither low temperatures during winter nor reproductive events in females during the summer led to irreversible damage to the photosynthetic apparatus. We conclude that (i) the Mediterranean dwarf palm, C. humilis, suffers from photoinhibition during winter, but this is transient and does not lead to irreversible damage, and (ii) females from this plant species are more sensitive than males to photoinhibition during reproductive events.